Local Symmetry Breaking Suppresses Thermal Conductivity in Crystalline Solids. Issue 15 (19th February 2022) - Dutta, Moinak; Prasad, Matukumilli V. D.; Pandey, Juhi; Soni, Ajay; Waghmare, Umesh V.; Biswas, Kanishka
Abstract: Understanding the correlations of both the local and global structures with lattice dynamics is critical for achieving low lattice thermal conductivity ( κ lat ) in crystalline materials. Herein, we demonstrate local cationic off‐centring within the global rock‐salt structure of AgSbSe2 by using synchrotron X‐ray pair distribution function analysis and unravel the origin of its ultralow κ lat ≈0.4 W mK −1 at 300 K. The cations are locally off‐centered along the crystallographic ⟨ 100 ⟩ direction by about ≈0.2 Å, which averages out as the rock‐salt structure on the global scale. Phonon dispersion obtained by density functional theory (DFT) shows weak instabilities that cause local off‐centering distortions within an anharmonic double‐well potential. The local structural distortion arises from the stereochemically active 5s 2 lone pairs of Sb. Our findings open an avenue for understanding how the local structure influences the phonon transport and facilitates the design of next‐generation crystalline materials with tailored thermal properties. Abstract : The globally rock‐salt material AgSbSe2 is found to be locally distorted due to the off‐centering of Sb atoms driven by a stereochemically active 5s 2 lone pair of electrons. This local off‐centering plays an important role in suppressing the thermal propagation, resulting in ultralow lattice thermal conductivity in AgSbSe2 .